Trojan horse in curricular Innovation: Meanings materialized in the classroom (Research, Society and Development, 2021)
Objective: to report the meanings manifested by students of the Curricular Innovation and Health Training component in a Graduate Program of a Federal University in northeastern Brazil. Methodology: report of experience produced from a thematic class on curricular innovations, developed with the participation of students of a graduate program in nursing and health in the stricto sensu modality. Data were collected and discussed from the semiotic analysis of images still in the drawings elaborated by the participants after the problematization of the subject. Results: it can be affirmed that new proposals for education have redirected the learning process, however there is coexistence of usual and innovative models and opportunities, and traditional training is represented more clearly, even when treated as a transformative possibility. Final considerations: it was verified the conviviality of several curricular theories in the ideary of the stricto sensu graduate students, that despite the advances, the traditional pedagogical practice still interferes in a hegemonic way in the conduction of the teaching-learning process, which requires a reorientation of the training in order to promote a conscious and solid change in the educational process.